Efficacy and Safety of Cenicriviroc in Patients With Primary Sclerosing Cholangitis: PERSEUS Study. Issue 3 (22nd December 2020) - Eksteen, Bertus; Bowlus, Christopher L.; Montano‐Loza, Aldo J.; Lefebvre, Eric; Fischer, Laurent; Vig, Pamela; Martins, Eduardo Bruno; Ahmad, Jawad; Yimam, Kidist K.; Pockros, Paul J.; Feld, Jordan J.; Minuk, Gerald; et al.
Abstract : Primary sclerosing cholangitis (PSC) is a chronic cholestatic disease with no approved treatments. C‐C chemokine receptor types 2 and 5 (CCR2/CCR5) play an important role in inflammation and fibrosis and are potential therapeutic targets for PSC. We evaluated the efficacy and safety of cenicriviroc (CVC), a dual antagonist of CCR2 and CCR5, for the treatment of PSC. This was a single‐arm, open‐label, exploratory study of CVC in adults with a clinical diagnosis of PSC, serum alkaline phosphatase (ALP) ≥1.5 times the upper limit of normal (ULN), with or without inflammatory bowel disease, across eight sites in the United States and Canada. The primary endpoint was percent change in ALP over 24 weeks; key secondary efficacy endpoints were proportion of participants who achieved ALP normalization and overall response (decrease to <1.5 times the ULN or 50% decrease). Of the 24 participants, 20 completed the study. The mean age was 43 years, 50% were female, and the mean body mass index was 25 kg/m 2 . From a median ALP baseline of 369 U/L (range: 173, 1, 377 U/L), a median absolute reduction of 49.5 U/L (range: −460, 416 U/L) was achieved at week 24, corresponding to a median reduction of 18.0% (range: −46%, 89%). No participant achieved ALP normalization or a 50% decrease; 2 participants (10%) achieved a reduction in ALP to < 1.5 times the ULN, and 4 had ≥25% increase. Twenty participants (83.3%) reported at least one adverse event; most were mild to moderate in severity. The most frequent events were rash, fatigue, and dizziness. Conclusion: After 24 weeks of CVC treatment, adults with PSC achieved a modest reduction (median 18%) in the surrogate endpoint of ALP. CVC was well tolerated, and no new safety signals were observed. ClinicalTrials.gov identifier: NCT02653625.